Investor Preferences in Choosing Digital Investment Applications: A Study on Banking and Non-Banking Securities Platforms - Novita Juni Astutik; Rahmat Setiawan (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The digital transformation has reshaped Indonesia’s retail investment landscape through the emergence of digital investment applications from both banking and non-banking institutions. Despite the growing adoption of such platforms, user preferences toward different types of applications remain underexplored. This study aims to examine the factors influencing user preferences in selecting digital investment applications, by comparing banking and non-banking securities platforms. A quantitative approach was employed, involving 124 active users of digital investment apps selected through purposive sampling. Five key variables were analyzed: ease of use, trust in technology, institutional trust, perceived financial benefit, and social influence. Data were analyzed using descriptive statistics and binary logistic regression. The findings reveal that most users prefer non-banking applications. Among the analyzed variables, institutional trust emerged as the most significant predictor of user preference. These findings suggest that digital investment platforms should focus not only on enhancing technological features, but also on strengthening institutional reputation and building user trust. These findings suggest the importance of incorporating institutional trust in the development of technology adoption models in the digital finance sector. Practically, app developers need to prioritize building institutional reputation and user trust, in addition to enhancing technological features.